Opposite Effects of Voluntary Physical Exercise on β3-Adrenergic Receptors in the White and Brown Adipose Tissue - Balagova, Lucia; Graban, Jan; Puhova, Agnesa; Jezova, Daniela (Hormone and Metabolic Research, 2019)
Catecholamine effects via β3-adrenergic receptors are important for the metabolism of the adipose tissue. Physical exercise is a core component of antiobesity regimens. We have tested the hypothesis that voluntary wheel running results in enhancement of β3-adrenergic receptor gene expression in the white and brown adipose tissues. The secondary hypothesis is that dietary tryptophan depletion modifies metabolic effects of exercise. Male Sprague-Dawley rats were assigned for sedentary and exercise groups with free access to running wheels for 3 weeks. All animals received normal control diet for 7 days. Both groups were fed either by low tryptophan (0.04%) diet or by control diet (0.2%) for next 2 weeks. The β3-adrenergic receptor mRNA levels in response to running increased in the retroperitoneal and epididymal fat pads. The gene expression of uncoupling protein-1 (UCP-1) was increased in the brown, while unchanged in the white fat tissues. Unlike control animals, the rats fed by low tryptophan diet did not exhibit a reduction of the white adipose tissue mass. Tryptophan depletion resulted in enhanced concentrations of plasma aldosterone and corticosterone, but had no influence on exercise-induced adrenal hypertrophy. No changes in β3-adrenergic receptor and cell proliferation measured by 5-bromo-2′-deoxyuridine incorporation in left heart ventricle were observed. The reduced β3-adrenergic receptor but not enhanced uncoupling protein-1 gene expression supports the hypothesis on hypoactive brown adipose tissue during exercise. Reduction in dietary tryptophan had no major influence on the exercise-induced changes in the metabolic parameters measured.
Keywords: tryptophan; diet; uncoupling protein-1; heart; gene expression